PERLINDUNGAN HUKUM DATA PRIBADI YANG DISALAHGUNAKAN UNTUK KEGIATAN PROSTITUSI - Aulia Dean Puspita Sari; Erny Herlin Setyorini (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
In this research, it has the aim of mentioning the regulation regarding personal data that is used by other people for prostitution activities according to written regulations in Indonesia or often referred to as positive law and to understand the form of legal protection for victims whose personal data is used for prostitution activities. In accordance with article 28G of the Constitution of the Republic of Indonesia which states that all people have the right to personal and family protection which is a human right. The type of research used in this study is normative legal research and for research it refers to the rules or norms that behave in society. This research is based on the regulations that apply, especially on the norms according to the law. The approach method used by the author is a case approach (casus approach) and a conceptual approach (conceptual approach). The results of this study, show the regulations for the use of personal data used by other people who are not responsible for committing crimes, especially in matters of identity fraud and legal protection of personal data and defamation for victims whose personal data is misused by others for acts of prostitution